Hubungan minat baca dan penguasaan diksi terhadap keterampilan membaca pemahaman kelas v SD negeri se-kecamatan karanganyar - Janika Yasin Hartiwi; St. Y. Slamet (Universitas Sebelas Maret, 2025)
The researcher applied a quantitative approach with a correlational design to see the relationship between reading interest and mastery of diction on reading comprehension skills. The sampling technique was probability sampling with the cluster random sampling method. Data were collected through reading comprehension and diction mastery skills tests and reading interest questionnaires. Data analysis techniques used descriptive and statistical analysis. Descriptive analysis techniques include average, maximum, minimum, mean, median, mode, variance, and standard deviation. Statistical analysis techniques include swimmer test analysis, simple analysis, and multiple analysis. Based on the calculation results, the results for the correlation of reading interest and mastery of diction on reading comprehension skills were obtained with a Sig. value of 0.000 and a Pearson correlation value of 0.910, which means there is a positive and significant relationship.Kata kunci: Correlation, reading interest, mastery of diction, reading comprehension skills, elementary school .